SpoOA represses transcription of the cry toxin genes in Bacillus thuringiensis - Poncet, Sandrine; Dervyn, Etienne; Klier, Andre; Rapoport, Georges (Microbiology (Society for General Microbiology), 1997)
Unité de Génétique Microbienne, Institut National de la Recherche Agronomique, Domaine de Vilvert, 78352 Jouy en Josas Cedex, France Unité de Biochimie Microbienne, Institut Pasteur, URA 1300 du Centre National de la Recherche Scientifique, 25 rue du Docteur Roux, 75724 Paris Cedex 15, France 1 Author for correspondence: Sandrine Poncet. Tel: +33 1 34 65 25 09. Fax: +33 1 34 65 25 21. e-mail: sponcet@biotec.jouy.inrefr ABSTRACT Summary: The DNA regions upstream from the genes encoding polypeptides of Bacillus thuringiensis subsp. israelensis larvicidal crystals (cry4A, cry4B, cry11A) contain sequences with similarities to the spoOA box of Bacillus subtilis (or OA box) and the promoter recognized by the H -associated RNA polymerase of B. subtilis . Expression of cry-lacZ transcriptional fusions was analysed in various B. thuringiensis genetic backgrounds. The early transcription of the toxin genes was not sporulation-dependent, whereas the late-stage expression at t 4-6 was E -dependent. Primer extension analysis confirmed that the cry4 -and cry11 -type toxin genes were weakly transcribed during the transition phase; expression analysis of a cry11A '-lacZ transcriptional fusion in B. subtilis sporulation mutants confirmed the involvement of the H -RNA polymerase. Primer extension analysis showed that in B. thuringiensis subsp. israelensis , the cry4A and cry11A gene transcription observed at the end of the growth stage was turned off at the beginning of the sporulation phase. The DNA region located upstream from the cry11A gene promoter including the putative OA box was deleted. This led to a derepression of the expression of the cry11A operon. These results suggest that the cry4A, cry4B and cry11A toxin genes of B. thuringiensis subsp. israelensis are transcribed during the transition phase by the RNA polymerase associated with the H factor and are subject to SpoOA repression. Keywords: Bacillus thungiensis, cry toxin genes, SpoOA, transcription